Unpacking the Role of Psychological Empowerment in Linking Job Autonomy to Performance: Insights from BUMDes Management - Bondan Subagyo; Indah Yuni Astuti (FKDP (Forum Komunikasi Dosen Peneliti), 2026)
This study aims to analyze the effect of job autonomy on employee performance, with psychological empowerment as a mediating variable among Village-Owned Enterprises (BUMDes) management personnel in Kunjang District, Kediri Regency. This research employs a quantitative approach with a population of 72 BUMDes management personnel. Data were analyzed using Structural Equation Modeling (SEM) with SmartPLS. The results indicate that job autonomy does not have a significant effect on psychological empowerment, suggesting that the level of autonomy provided does not directly enhance the psychological empowerment of management personnel. In addition, job autonomy does not significantly affect employee performance, indicating that greater freedom at work has not yet translated into improved productivity, responsiveness, and accountability. However, psychological empowerment has a significant effect on employee performance, confirming that the dimensions of Meaning, Competence, Self-Determination, and Impact play an important role in improving performance. Furthermore, psychological empowerment is not able to mediate the relationship between job autonomy and employee performance, indicating that other factors may be more dominant in determining the effectiveness of job autonomy. The findings imply the importance of improving governance, strengthening policy support, and enhancing the competencies of BUMDes management personnel to achieve more optimal performance.